Molecular Details of Retinal Guanylyl Cyclase 1/GCAP-2 Interaction - Rehkamp, Anne; Tänzler, Dirk; Iacobucci, Claudio; Golbik, Ralph P.; Ihling, Christian H.; Sinz, Andrea (Frontiers in Molecular Neuroscience, 2018)
The rod outer segment guanylyl cyclase 1 (ROS-GC1) is an essential component of photo-transduction in the retina. In the light-induced signal cascade, membrane-bound ROS-GC1 restores cGMP levels in the dark in a calcium-dependent manner. With decreasing calcium concentration in the intracellular compartment, ROS-GC1 is activated via the intracellular site by guanylyl cyclase-activating proteins (GCAP-1/-2). Presently, the exact activation mechanism is elusive. To obtain structural insights into the ROS-GC1 regulation by GCAP-2, chemical cross-linking/mass spectrometry studies using GCAP-2 and three ROS-GC1 peptides were performed in the presence and absence of calcium. The majority of cross-links were identified with the C-terminal lobe of GCAP-2 and a peptide comprising parts of ROS-GC1’s catalytic domain and C-terminal extension. Consistently with the cross-linking results, surface plasmon resonance and fluorescence measurements confirmed specific binding of this ROS-GC peptide to GCAP-2 with a dissociation constant in the low micromolar range. These results imply that a region of the catalytic domain of ROS-GC1 can participate in the interaction with GCAP-2. Additional binding surfaces upstream of the catalytic domain, in particular the juxtamembrane domain, can currently not be excluded.